The Role of Cytokines, Hormones, and Cellular Regulation in Improving Maternal and Fetal Well-Being - Hariyasa Sanjaya, I Nyoman; Sutandi, Chatrine; Syauta, Fetrisya (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2024)
Maternal and fetal well-being is a complex interplay of various factors. A key factor is that women receiving early and adequate pregnancy care are more likely to achieve positive pregnancy outcomes. Several studies have identified internal maternal factors as significant contributors to the well-being of both mother and fetus. However, scientific research and discussions on the role of cytokines, hormones, and cellular regulation in maternal and fetal well-being outcomes still need to be completed. Progesterone, a vital hormone for pregnancy and humans, influences immune function directly and through mediators by promoting the synthesis of T helper cell-type cytokines. The favorable benefits of dydrogesterone on repeated spontaneous miscarriages and impending miscarriages may be attributed to the regulating effects of these cytokines and the hormone's capacities. T helper cell-produced cytokines are linked to allograft rejection. Lastly, our finding of cellular regulatory mechanisms, including apoptosis, autophagy, and cellular senescence, highlights the multifaceted nature of maintaining maternal and fetal health during pregnancy. This review aims to delve deeper into the role of cytokines, hormones, and cellular regulation in enhancing maternal and fetal well-being.